2020
DOI: 10.1155/2020/6212935
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Cancerous Mitochondria and Suppression of Tumor Growth Using Redox-Active Treatment Adjuvant

Abstract: Redox-active substances and their combinations, such as of quinone/ascorbate and in particular menadione/ascorbate (M/A; also named Apatone®), attract attention with their unusual ability to kill cancer cells without affecting the viability of normal cells as well as with the synergistic anticancer effect of both molecules. So far, the primary mechanism of M/A-mediated anticancer effects has not been linked to the mitochondria. The aim of our study was to clarify whether this “combination drug” affects mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 132 publications
2
46
0
Order By: Relevance
“…This is direct evidence that menadione does not act as a coagulant when used in combination with ascorbate in doses with a pronounced anticancer effect. M/A at concentrations up to 20/2000 µM/µM, exceeding those that can be achieved pharmacologically, did not affect the viability of normal human lymphocytes and normal human epithelial cells, which was analyzed in vitro in our previous study [46,65].…”
Section: Effect Of M/a On Tumor Growth and Survival Of Glioblastoma-b...mentioning
confidence: 95%
See 3 more Smart Citations
“…This is direct evidence that menadione does not act as a coagulant when used in combination with ascorbate in doses with a pronounced anticancer effect. M/A at concentrations up to 20/2000 µM/µM, exceeding those that can be achieved pharmacologically, did not affect the viability of normal human lymphocytes and normal human epithelial cells, which was analyzed in vitro in our previous study [46,65].…”
Section: Effect Of M/a On Tumor Growth and Survival Of Glioblastoma-b...mentioning
confidence: 95%
“…This effect is thought to be due to the redox cycling between the two molecules in the cells and the extracellular environment, which requires an excess of ascorbate and leads to the overproduction of ROS (Figure S1, see the Supporting Materials). The mechanism and the combination index are described in many articles summarized recently in [46]. M/A has attracted the attention of researchers due to the synergistic anticancer effect of the two molecules, as well as its ability to kill cancer cells without affecting the viability of normal cells [46].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results similarly showed a specific cooperative effect on HR + /HER2 − cells (MCF7), while preserving normal control fibroblasts. To further support our theory, it is of interest to cite Bakalova et al, who demonstrated that using menadione/ascorbate in combination with 13 conventional clinically used drugs for leukemia treatment did not induce cytotoxicity in cancer cells, but instead, caused irreversible metabolic changes, increasing sensitivity toward conventional therapy [23]. These observations are particularly important because they lay the foundations for future use of extracts to enhance the effects of clinically used drugs that act on breast cancer cells through the induction of oxidative stress, such as tamoxifen (used for hormonal therapy) or paclitaxel (used for chemotherapy).…”
Section: Discussionmentioning
confidence: 52%